Nietzsche and modern times : a study of Bacon, Descartes, and Nietzsche - Lampert, Laurence, 1941- (Yale University Press, 1993)
This book explores the character of modernity through a consideration of Bacon, Descartes, and Nietzsche. It argues that Bacon and Descartes, in their positive claims for science, played the fundamental role in the development of the modern world view; that they used the Platonic art of dissimulative writing as the means to achieve their ends by making their revolutionary aims appear compatible with Christianity; and that Nietzsche understood both their ends and their means and set out to ground an antimodern world view.